Antimicrobial Resistance, Virulence, and Genetic Characterization of Methicillin-Resistant Staphylococcus aureus Recovered from Ready-to-Eat (RTE) Food in China: A New Challenge for Food Safety - Wei Wang; Hui Li; Changwei Wang; Fengqin Li; Yinping Dong; Jing Xiao (Zoonoses)
The objective of the present study was to determine the prevalence, antimicrobial resistance, virulence profiles, and molecular characteristics of methicillin-resistant Staphylococcus aureus (MRSA) obtained from ready-to-eat (RTE) foods in China. Two hundred seventy-six RTE food-associated S. aureus isolates were collected from 25 provinces across China in 2018, then characterized by antimicrobial susceptibility testing, virulence factors detecting, multilocus sequence typing (MLST), spa typing, SCC mec typing and pulsed-field gel electrophoresis (PFGE). Two hundred fifty isolates (90.6%) were resistant to at least one antimicrobial agent; 73 (26.4%) isolates were multi-drug resistant (MDR). Thirty MRSA isolates were identified, among which nine toxin genes ( sea, seb, sec, sed, seh, selk, sell, selq , and tsst-1 ) were detected. Sixty percent (18/30) of the MRSA isolates harbored multiple toxin genes. Four virulence gene patterns were identified, with seb-selk-selq (30/30) being the most common pattern. Thirteen sequence types, as well as 13 spa and 4 SCC mec types were found among 30 MRSA isolates. The most prevalent MRSA lineages were CC59-t437-SCC mec IV/V (23.3% [7/30]), CC398-t011-SCC mec V (23.3% [7/30]), and CC1-t114-SCC mec IV (16.7% [5/30]). Our findings highlight the importance for the identification of prevalent clones, assessment of drug-resistance and virulence, and formulation of food safety measures for public health.